2021
DOI: 10.1007/s12206-021-2103-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of processing parameters on creep behavior of 316L stainless steel produced using selective laser melting

Abstract: The selective laser melting (SLM) method is being increasingly applied in the aerospace and power industries for the production of high temperature critical components. The effects of SLM processing parameters, such as laser power, scanning speed, and energy density on the creep properties were investigated for 316L stainless steel (SS316L). The effect of building direction was also studied. The creep resistance was influenced by the manufacturing direction. The vertical specimen demonstrated a longer creep li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…For instance, it is uncertain how the overall porosity level can affect creep life and whether there is a certain threshold where microstructural features can dominate over the porosity level. One example would be a study like the one on LPBF 316L by Bae et al as shown in Fig . 37 [157]. The authors found that the creep behavior was closely related to the density of the sample tested.…”
Section: Creep Responsementioning
confidence: 97%
See 2 more Smart Citations
“…For instance, it is uncertain how the overall porosity level can affect creep life and whether there is a certain threshold where microstructural features can dominate over the porosity level. One example would be a study like the one on LPBF 316L by Bae et al as shown in Fig . 37 [157]. The authors found that the creep behavior was closely related to the density of the sample tested.…”
Section: Creep Responsementioning
confidence: 97%
“…As can be observed in the table, growth and coalescence of pores are often responsible for creep failure [155,156]. Additionally, pores can also act as crack initiation sites that lead to premature creep fracture [155,157]. For example, Xu et al investigated the effect of heat treatment (homogenization, solution treatment and single-ageing) and surface finish on creep behavior of LPBF IN718 at 750 MPa and 650 °C, and found that while cracks often originate from the surface (with pre-existing cracks also caused by machining), porosity in the material can grow, coalescence and eventually lead to the fracture of the cross-section as illustrated in Fig.…”
Section: Creep Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The results are shown in Figure 7. Although the materials and the SLM processing parameters of the three specimens were the same, the normalized nonlinear coefficients always fluctuated at a certain level; the primary reason for this fluctuation is that the microstructure of tested specimens presented typical anisotropic characteristics [31][32][33][34]. Due to a high-energy laser beam being used as a mobile heat source during the process of the formation of the 316L stainless steel specimen using SLM technology, and through rapid heating, melting, and solidification, extreme non-equilibrium conditions were produced during the material's processing.…”
Section: Nonlinearity Coefficients In the Slm 316l Stainless Steel Sp...mentioning
confidence: 99%